COVID-19 pandemic’s impact on networks of depression and anxiety in naturalistic transdiagnostic sample of outpatients with non-psychotic mental illness - Kim, Shin Tae; Seo, Jun Ho; Park, Chun Il; Kim, Se Joo; Kang, Jee In (Frontiers in Psychiatry, 2023)
The 2019 coronavirus disease (COVID-19) pandemic has caused an unprecedented disruption of daily lives and a mental health crisis. The present study examined how the depression and anxiety symptom network changed during the COVID-19 pandemic in a naturalistic transdiagnostic sample with non-psychotic mental illness. A total of 224 psychiatric outpatients before the pandemic and 167 outpatients during the pandemic were included in the study and were assessed for the Patient Health Questionnaire and the Beck Anxiety Inventory. The network of depression and anxiety symptoms before and during the pandemic were estimated separately and were assessed differences. The network comparison analysis showed a significant structural difference between the networks before and during the pandemic. Before the pandemic, the most central symptom in the network was feelings of worthlessness, while in the during pandemic network, somatic anxiety emerged as the most central node. Somatic anxiety, which showed the highest strength centrality during the pandemic, showed significantly increased correlation with suicidal ideation during the pandemic. The two cross-sectional network analyses of individuals at one point in time cannot demonstrate causal relationships among measured variables and cannot be assumed to generalize to the intraindividual level. The findings indicate that the pandemic has brought a significant change in the depression and anxiety network and somatic anxiety may serve as a target for psychiatric intervention in the era of the pandemic.